Determining the Amino Acid Digestibility of Soybean Meal from Different Midwest Soybean Varieties Fed to Broilers - Kara M. Dunmire; Michaela B. Braun; Caitlin E. Evans; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
At hatch, 240 one-day old Cobb500 male broilers were placed in battery cages to determine soybean meal (SBM) apparent ileal digestibility (AID) of amino acids (AA). There were 6 broilers per cage and 10 replicates per treatment. A common corn-SBM crumble starter diet was fed from d 0 to 10 with experimental mash diets fed from d 10 to 18 with SBM as the only source of AA. Dietary treatments consisted of 1 of 4 soybean sources varying in quality determined by crude protein (CP) content and processed into SBM. Dietary treatments consisted of a commercially processed SBM with 47% CP (CSBM) or experimentally processed SBM with 42% CP (42SBM), 49% (49SBM), or 52% CP (52SBM). Two sources consisted of soybeans from a similar region and were processed either commercially (CSBM) or experimentally (49SBM) solvent extracted at Texas A&M University. Additional sources included a low quality (42SBM) and highquality (52SBM) soybean, experimentally solvent extracted into SBM at a pilot-scale facility at Texas A&M University. Dietary treatments were dextrose and SBM-based, and consisted of 1 of 4 SBM sources included in diets formulated to 20% CP. On d 18, broilers were euthanized by CO2inhalation and ileal samples were collected for determination of AID of AA. Soybean meal processed from low, medium, and high CP soybeans resulted in increased concentrations of crude protein and indispensable AA. Individual SBM samples indicated that SBM with higher CP had lower NDF. Data were analyzed using the GLIMMIX procedure in SAS 9.4, with cage as the experimental unit, cage location as the blocking factor with Tukey-Kramer adjustment for multiple comparisons used. For soybeans grown in a similar region, broilers fed CSBM, processed conventionally, had increased (P<0.05) AID of total AA, Arg, His, Lys, and Thr compared to 49SBM, processed experimentally. Increasing the CP content of SBM from 42SBM, and 49SBM, to 52SBM increased (P<0.05) AID of total AA, Arg, His, Leu, Lys, Thr, and Val. Broilers fed CSBM, 49SBM, and 52SBM had increased (P<0.001) Ile, Met, Phe, and Trp compared to broilers fed 42SBM. In conclusion, CSBM and 49SBM were sourced from a similar location but processed either commercially or experimentally, respectively. Commercially processed SBM had improved AID AA compared to the experimentally processed SBM. Additionally, SBM with increasing concentrations of CP and AA had improved AID of AA.
Keywords: amino acid digestibility; soybean meal quality; broilers; poultry